Girls in Traditional and Gender-Responsive Juvenile Justice Placements - Smith, Paula (Women & criminal justice, 2017)
There is no shortage of policy, research, or practice recommendations for implementing gender-responsive programming. There is, however, substantial variation in the way in which gender-responsive has been defined and operationalized in practice. This exploratory study represents an examination of girls’ lived experiences in traditional and gender-responsive juvenile justice programs from an insider’s perspective. Participants’ narratives were overwhelmingly positive about gender-responsive programming; however, the findings in this study also suggest that it is critical to incorporate important gender-neutral skills into gender-responsive programming to enable girls to succeed economically and interdependently as they attempt to maintain themselves and their families once they are released from custody.